Characterization of soil fertility in a Eucalyptus dunnii Maiden stand in Pampa biome of Rio Grande do Sul state - Dick, Grasiele; Schumacher, Mauro Valdir; Momolli, Dione Richer (Revista Ecologia e Nutrição Florestal - ENFLO, 2016)
Monitoring ecological aspects, such as chemical soil quality, can provide subsidies for silvicultural management and soil conservation, to maintain the productivity of forest sites. This study aimed to evaluate changes in soil chemical properties in a Eucalyptus dunnii stand, in two and five-year-old, in the Pampa biome of Rio Grande do Sul state. Therefore, at two and the five-year-old stand soil samples were collected at five depths (0-20, 20-40, 40-60, 60-80 e 80-100 cm), with subsequent determination of physical attributes and pH, organic matter, content of aluminum, calcium, magnesium, potassium and phosphorus, as well as potential and effective CEC, base saturation and aluminum saturation. We applied the t-test (α = 5%) to detect significant differences in the properties of soil in function of time. The soil chemical analysis revealed that, on both occasions, there were low levels of nutrients, organic matter as well as acid pH, and high aluminum saturation. After three years of growth of Eucalyptus dunnii trees, the pH decreased in all soil depths, Ca and K decreased by 20-40 cm and 0- 20 cm, respectively. The aluminum content increased at all depths, as well as phosphorus and organic matter from 40 to 100 cm of soil. After three years of the first evaluation of the soil, there was change of fertility, especially in pH, organic matter and phosphorus and potassium contents.